Peran Maqashid al-Syari’ah dalam Pencegahan Kekerasan Seksual dan Pergaulan Bebas - sri Hidayanti; Herdiansyah (Jurnal Indragiri Penelitian Multidisiplin, 2023)
This paper analyzes the role of maqashid al-syariah by maintaining five main points in relation to sexual violence and promiscuity that occurs in society. To find the answer to the analysis, the library research method was used by reviewing and referring directly to primary and secondary references in the study of Maqashid Syari'ah. The results of the analysis show that maqashid al-syariah has a role in maintaining five main things to review as a preventive in sexual violence and promiscuity. Maqashid al-Sharia is a concept that emphasizes the purpose of establishing Islamic law in an effort to maintain the benefit of human life, with the aim of bringing benefits and avoiding harm. To maintain the continuity and dynamism of Islamic Shari'a in the present context, maqashid al-Sharia is absolutely necessary.